2012
DOI: 10.1155/2012/378415
|View full text |Cite|
|
Sign up to set email alerts
|

Ethanol Extracts of Fruiting Bodies ofAntrodia cinnamomeaSuppress CL1-5 Human Lung Adenocarcinoma Cells Migration by Inhibiting Matrix Metalloproteinase-2/9 through ERK, JNK, p38, and PI3K/Akt Signaling Pathways

Abstract: Cancer metastasis is a primary cause of cancer death. Antrodia cinnamomea (A. cinnamomea), a medicinal mushroom in Taiwan, has shown antioxidant and anticancer activities. In this study, we first observed that ethanol extract of fruiting bodies of A. cinnamomea (EEAC) exerted a concentration-dependent inhibitory effect on migration and motility of the highly metastatic CL1-5 cells in the absence of cytotoxicity. The results of a gelatin zymography assay showed that A. cinnamomea suppressed the activities of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 48 publications
6
40
1
Order By: Relevance
“…Prior results have shown that elevated MMP-2 and -9 was observed in late stages of cancer, which could be a prognostic factor in several human cancers (17). Furthermore, prevention of lung cancer metastasis by inhibition of MMP-2 and/or MMP-9 by bioactive compounds isolated from plants and herbs has been previously demonstrated (18,19). Extracts from Antrodia cinnamomea displayed antimetastatic effects by the supersession of MMP-2 and -9 activities (18,19).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prior results have shown that elevated MMP-2 and -9 was observed in late stages of cancer, which could be a prognostic factor in several human cancers (17). Furthermore, prevention of lung cancer metastasis by inhibition of MMP-2 and/or MMP-9 by bioactive compounds isolated from plants and herbs has been previously demonstrated (18,19). Extracts from Antrodia cinnamomea displayed antimetastatic effects by the supersession of MMP-2 and -9 activities (18,19).…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, prevention of lung cancer metastasis by inhibition of MMP-2 and/or MMP-9 by bioactive compounds isolated from plants and herbs has been previously demonstrated (18,19). Extracts from Antrodia cinnamomea displayed antimetastatic effects by the supersession of MMP-2 and -9 activities (18,19). Furthermore, fisetin and myricetin inhibited the nuclear translocation of NF-κB, c-Fos and c-Jun, decreased the expression and activities of MMP-2 and urokinase-type plasminogen activator, and eventually attenuated the migration and metastasis of lung A549 cells (20,21).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, many natural extracts have been demonstrated to inhibit migration in various cancer cells via PI3K/AKT, a downstream pathway of FAK [34][35][36][37]. The activity of RhoGTPase proteins is also regulated by the function of activated Akt (pAkt) [38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of studies have shown that the PI3K/AKT signaling pathway may modulate the expression of MMPs, as well as TIMPs, to promote the degradation of ECM proteins, and this mechanism was essential for invasion of human tumors, including lung cancer (13,23). To the best of our knowledge, allicin has been confirmed to inhibit the PI3K/AKT signaling pathway in the HepG2 cell line; however, it remains unknown whether such an effect also exists in lung adenocarcinoma (17).…”
Section: Discussionmentioning
confidence: 99%